BAKTERI AEROB PATOGEN DAN UJI KEPEKAAN ANTIMIKROBA DI RUANGAN PERAWATAN PENYAKIT DALAM - Fedelia Raya; Nurhayana Sennang; Suci Aprianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Pathogenic bacteria are the major causes of airborne infection at the hospital ward. Nosocomial infection can occur at the opened as well as at the closed room. Nosocomial infection influences the morbidity and mortality in the hospital and need an extra attention, because of the increased number of hospital patients, micro organism mutation and increased of bacteria resistance to antibiotics. The aim of this study was to quantify the number of aerobic bacteria, and to know the pathogenic bacteria identification and its determination on the susceptibility of the antimicrobial problems at the internal medicine ward. This research was carried by a cross sectional study, which performed by collecting air samples in eight internal medicine ward of Dr. Wahidin Sudirohusodo Hospital using Microbiology Air Sampler 100 (MAS 100). The bacterial identification and the antimicrobial susceptibility test (AST) were conducted at the Balai Besar Laboratorium Kesehatan (July to August 2009). In this study were found the numbers of bacteria colonies about 580–6040 CFU/m3. The pathogenic bacteria that identified were Acinetobacter calcoaceticus, Staphylococcus saprohpyticus, Enterobacter hafniae and Stomatococcus mucilaginosus that were sensitive to Amikasin, Gentamicyn, Azitromycin and Norfloxacyn but resistant to Ampicillin. The number of bacterial colonies exceeded the established number standard by Decree of the Indonesian Health Minister. The pathogenic bacteria showed the most sensitive result of AST were Acinetobacter calcoaceticus, Enterobacter hafniae, Stomatococcus mucilaginosus and Staphylococcus saprohpyticus.